Quantitative Sum Product Estimates on Different Sets - Shen, Chun-Yen (The Electronic Journal of Combinatorics, 2008)
Let F_p be a finite field of p elements with p prime. In this paper we show that for A ,B F_p with |B|≤ |A| < p^1 2 then (|A+B|, |AB|) (|B|^14 |A|^13 )^1/18|A|. This gives an explicit exponent in a sum-product estimate for different sets by Bourgain.